2008
DOI: 10.4269/ajtmh.2008.78.426
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Immunogenicity of a Tetravalent Live-attenuated Dengue Vaccine in Flavivirus Naive Children

Abstract: A live-attenuated tetravalent dengue virus (DENV) vaccine candidate has been well tolerated and immunogenic in healthy, US flavivirus naive adult volunteers. We conducted a pilot, safety, and immunogenicity trial of the vaccine candidate in healthy Thai children (6-7 years of age) to prepare for its eventual evaluation in Thai infants. In an uncontrolled, open clinical trial, the investigational vaccine was administered on study Days 0 and 180 to seven volunteers residing in Bangkok without neutralizing antibo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
88
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 94 publications
(91 citation statements)
references
References 16 publications
2
88
0
1
Order By: Relevance
“…On each of the days that the DENV vaccine was formulated, retained samples of tetravalent product were frozen at −70°C, subsequently transported to WRAIR on dry ice, and returned to −70°C storage until thawed for potency testing using an immunofocus assay (IFA) as previously described. 12 Control vaccines. Varicella ( Varilrix ; GSK, Rixensart, Belgium) and H. influenzae type B ( Hiberix ; GSK, Rixensart, Belgium) vaccines(0.5-mL dose vial) were used as control vaccines for DENV vaccine doses 1 and 2, respectively.…”
Section: Safety and Immunogenicity Of A Tetravalent Live-attenuated Dmentioning
confidence: 99%
See 3 more Smart Citations
“…On each of the days that the DENV vaccine was formulated, retained samples of tetravalent product were frozen at −70°C, subsequently transported to WRAIR on dry ice, and returned to −70°C storage until thawed for potency testing using an immunofocus assay (IFA) as previously described. 12 Control vaccines. Varicella ( Varilrix ; GSK, Rixensart, Belgium) and H. influenzae type B ( Hiberix ; GSK, Rixensart, Belgium) vaccines(0.5-mL dose vial) were used as control vaccines for DENV vaccine doses 1 and 2, respectively.…”
Section: Safety and Immunogenicity Of A Tetravalent Live-attenuated Dmentioning
confidence: 99%
“…12 After a review of medical history and physical examination (subjects were to be in good general health), screening tests included a complete blood count (CBC with white blood cell differential and platelet count), alanine aminotransferase (ALT), aspartate aminotransferase (AST), hepatitis B surface antigen, antibody to human immunodeficiency virus (HIV), and antibody to hepatitis C virus. Those with normal test results were further screened to exclude those with pre-existing antibody to DENV-1, -2, -3, or -4 or Japanese encephalitis virus (JEV) by hemagglutination inhibition (HAI) and 50% plaque reduction neutralization test (PRNT 50 ).…”
Section: Safety and Immunogenicity Of A Tetravalent Live-attenuated Dmentioning
confidence: 99%
See 2 more Smart Citations
“…A single formulation was advanced for testing in flavivirus-naïve toddlers and children in Thailand. Two vaccine doses administered on a 0 and 6 month schedule were well tolerated and immunogenic [46,47]. A third dose of vaccine in the Thai studies demonstrated no sustainable immunogenicity impact (Thomas, S., personal communication).…”
Section: Live Virus Vaccine Attenuated By Cell Culture Passage-waltermentioning
confidence: 99%